Design of DC Motor Using Local Materials. - Ndyamuhaki, Bruce (Kabale University, 2024)
This project explores the design and construction of a DC motor using unconventional materials, including wood, magnets, copper wires, and plastic tubes. The motor's performance and efficiency are evaluated and the results demonstrate a functional DC motor with efficiency within the expected range for do-it-yourself DC motors. This project showcased an innovative approach to motor design and construction, highlighting the potential for creative problem-solving and resourcefulness in engineering applications. The successful completion of this project provides a foundation for future improvement and retirement paving the way for potential applications in educational settings do it yourself enthusiasts, and sustainable engineering solutions